Analisis Penambahan Serat Strapping Band Rigid Pavement Terhadap Kuat Lentur Beton - Muh. Fajar; Adnan Adnan; Hamka Hamka (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of science, especially in the field of transportation, especially roads, requires adequate infrastructure in the form of roads or pavement that is suitable for the conditions in the field. This research aims to determine the analysis of the addition of strapping band fibers on the flexural strength of concrete, the variation in influence is 0.5%, 1 .0%, 1.5%, the best composition for making rigid pavement flexural strength. This research uses experimental research methods, namely research in the laboratory which aims to investigate the effects of each other and compare the results. The research results of 4 variations, namely 0% (normal), 0.5%, 1.0% and 1.5% of fine aggregate, in testing concrete aged 28 days on normal concrete were 3.333 Mpa, for variations of 0.5% on average an average of 2,800 Mpa, a 1.0% variation an average of 2,133 MPa, and a 1.5% variation an average of 1,333 MPa. So it can be concluded that concrete with a variation of 0.5% achieves the design strength and is suitable for use. Meanwhile, variations of 1.0%, 1.5% do not reach the design compressive strength and are not suitable for use in construction.